A strategy to improve treatment‐related mortality and abandonment of therapy for childhood ALL in a developing country reveals the impact of treatment delays. Issue 8 (24th March 2015) - Suarez, Amaranto; Piña, Martha; Nichols‐Vinueza, Diana X.; Lopera, John; Rengifo, Lyda; Mesa, Mauricio; Cardenas, Marcela; Morrissey, Lisa; Veintemilla, Galo; Vizcaino, Martha; Del Toro, Ligia; Vicuna, Victor; et al.
<x xml:space="preserve">Abstract</x> Background Treatment‐related mortality and abandonment of therapy are major barriers to successful treatment of childhood acute lymphoblastic leukemia (ALL) in the developing world. Procedure A collaboration was undertaken between Instituto Nacional de Cancerologia (Bogota, Colombia), which serves a poor patient population in an upper‐middle income country, and Dana‐Farber/Boston Children's Cancer and Blood Disorders Center (Boston, USA). Several interventions aimed at reducing toxic deaths and abandonment were implemented, including a reduced‐intensity treatment regimen and a psychosocial effort targeting abandonment. We performed a cohort study to assess impact. Results The Study Population comprised 99 children with ALL diagnosed between 2007 and 2010, and the Historic Cohort comprised 181 children treated prior to the study interventions (1995–2004). Significant improvements were achieved in the rate of deaths in complete remission (13% to 3%; P = 0.005), abandonment (32% to 9%; P < 0.001), and event‐free survival with abandonment considered an event (47% to 65% at 2 years; P = 0.016). However, relapse rate did not improve. Medically unnecessary treatment delays were common, and landmark analysis revealed that initiating the PIII phase of therapy ≥4 weeks delayed predicted markedly inferior disease‐free survival (P = 0.016). Conversely, patients who received therapy without excessive delays had outcomes approaching those achieved in high‐income countries. Conclusions Implementation of a twinning program was followed by reductions in abandonment and toxic deaths, but relapse rate did not improve. Inappropriate treatment delays were common and strongly predicted treatment failure. These findings highlight the importance of adherence to treatment schedule for effective therapy of ALL. Pediatr Blood Cancer 2015;62:1395–1402. © 2015 Wiley Periodicals, Inc.